Influence of Transcranial Direct Current Stimulation Dosage and Associated Therapy on Motor Recovery Post-stroke: A Systematic Review and Meta-Analysis - Chow, Alan-Michael D.; Shin, Jeonghwa; Wang, Hongwu; Kellawan, Jeremy Mikhail; Pereira, Hugo M. (Frontiers in Aging Neuroscience, 2022)
Purpose: 1) To determine the impact of transcranial direct current stimulation (tDCS) applied alone or combined with other therapies on the recovery of motor function after stroke; 2) To determine tDCS dosage effect. Methods: Randomized controlled trials comparing effects of tDCS with sham using the Barthel Index (BI), upper and lower extremity Fugl-Meyer Assessment (FMA) and Modified Ashworth Scale (MAS), were retrieved from PubMed, Medline (EBSCO), and CINAHL from their inception to June 2021. Calculations for each assessment were done for the overall effect and associated therapy accounting for the influence of stroke severity or stimulation parameters. Results: 31 studies involving metrics of the BI, upper extremity FMA, lower extremity FMA and MAS were included. tDCS combined with other therapies was beneficial when assessed by the BI (mean difference: 6.8; P < 0.01) and these studies typically had participants in the acute stage. tDCS effects on the upper and lower extremity FMA are unclear and differences between sham and tDCS groups, as well as differences in the associated therapy type combined with tDCS potentially influenced the FMA results. tDCS was not effective compared to sham for the MAS. Stimulation types (e.g. anodal vs cathodal) did not influence these results and dosage parameters were not associated with the obtained effect sizes. Conventional therapy associated with tDCS typically produced greater effect size than assisted therapy. The influence of stroke severity is unclear. Conclusion: Potential benefits of tDCS can vary depending on assessment tool used, duration of stroke and associated therapy. Mechanistic studies are needed to understand potential role of stimulation type and dosage effect after stroke. Future studies should carefully conduct group randomization, control for duration of stroke and report different motor recovery assessments types.